Legal Awareness of Halal Products Certification among East Java Business Operators and Society - Khusniati Rofiah; Sri Lumatus Sa'adah; Martha Eri Safira; Abid Rohmanu; Azme Bin Haji Matali (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The number of business operators in East Java increases significantly each year but is unfortunately not accompanied by increased legal awareness. While many business operators are aware of the halal certification obligation, they need to actually comply to it. This research was conducted in East Java on 111 micro and small business operators and medium-sized enterprises (MSMEs) spread across several cities. A total of 450 respondents of various backgrounds who, at the time of research, had run their business for at least two years were involved in direct interviews and questionnaire surveys. This research focuses on discussing the awareness of business operators and the community in East Java based on Soerjono Soekanto's legal awareness (understanding, knowledge, obedience, and legal attitudes), and maqasid sharia. Efforts to increase knowledge and understanding of business owners of legal awareness still lacked due to non-existent sanctions and incomprehensive campaign. Meanwhile, in legal culture, there is a perception that food consumed by the community is not necessarily halal-certified. The government strategy to advocate legal awareness of halal product certification includes product acceleration through the halal product information (SIP Halal) system that is easily accessible to MSMEs.